(untitled) (Asian Journal of Social Science Studies, 2016)
Comparing with Ancient Chinese, passive sentences in Modern Chinese have been increasingly used, and patient subjects in them are not limited to noun phrases with a high animacy and the binding force for the sentential meaning of “suffering” and “misfortune” has largely loosened as well. As the commonest pattern in passive sentences, the same case for “Bei” (被) Passives. It is well known that “Bei” (被) Passives is a sort of difficult syntax pattern in teaching Chinese as a foreign language, and errors often occur in the use of “Bei” (被) Passives for a large number of second language learners who take Chinese as their target language. We admit that the usage of “Bei” (被) Passives has a certain connection with the linguistic animacy, while the reason for errors occur in this Chinese sentence “Wo (我) zai (在) dianti (电梯) kou (口) bei (被) ren (人) xiao (笑) le (了) xiao (笑)” is the semantic feature constraint.